ENHANCING FINANCIAL PERFORMANCE: THE ROLE OF FINANCIAL LITERACY AND DIGITAL TRANSFORMATION IN MAKASSAR'S SMES - Irmayanti, Irmayanti (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study examines the impact of financial literacy and digital transformation on the financial performance of small and medium enterprises (SMEs) in Makassar. Utilizing a sample of 150 SMEs, the research employs descriptive statistics, correlation analysis, and regression analysis to analyze the relationships between the variables. The findings reveal that the average financial literacy score is 68%, indicating a moderate level of financial knowledge among respondents. Significant positive correlations were observed between financial literacy, digital transformation, and financial performance, with regression analysis confirming that both financial literacy (β = 0.35, p < 0.01) and digital transformation (β = 0.30, p < 0.01) are critical determinants of financial performance. Qualitative feedback emphasizes the necessity for government support and training programs to enhance financial literacy and digital skills. The results highlight the importance of targeted interventions to foster sustainable growth in SMEs, underscoring that improving financial literacy and embracing digital technologies are essential strategies for enhancing financial outcomes in this sector